THE PROCESS OF POLYANILINE FORMATION WITH POLYACID - D.A. Karimova; L.M. Usmonova (Western European Studies, 2025)
Polyanilines and interpolymer complexes based on them can be synthesized both by chemical methods and through the electrochemical polymerization of aniline in a mother liquor on the electrodes of an electrochemical cell [1,2]. The electrochemically obtained electrically conductive interpolymer complexes of polyanilines with polyacids possess significant physicochemical properties compared to chemically synthesized compounds
Keywords: properties; interpolymer; liquor